Integrated Kampong City Block in Kampong Bandur District of Medan Maimun - Dwira Nirfalini Aulia; Nadiatul Khairiah (International Journal of Architecture and Urbanism, 2017)
Kampong Badur precisely is one of the slums in Medan City with the category of slum 'very bad' based on the Office of Housing and Settlements Medan 2015. Given the issues in various developing countries precisely in big cities in Indonesia are the increase of population and the process of urbanization. For that, the selection of strategies relating to the rearrangement by improving the old function and adding a new function is the strategy of Redevelopment. An urban redevelopment project that refers to the typical residential vernacular city of Indonesia called Kampong. So, in overcoming the problem of urban slum dwelling in low-income villagers who still put forward the typical residential vernacular Indonesia (kampong) is Kampong City Block. The concept of Kampong City Block is combined with the concept of economic improvement to overcome the problems of lowincome population slum area. In the case of Kampong Badur, social mapping in terms of livelihoods obtained some livelihoods that are considered to support the economic development of the population of trade, farming, chicken breeding, and small convection industry. The integration of these 4 sectors will be synergized in every design process. Then, the concept of Integrated Kampong City Block is also maintaining socio-culture of Badur people so that the approach to the theme of behavioral architecture and analysis of all aspects of the village community, ranging from the concept of macro and micro.